Late-afternoon endurance exercise is more effective than morning endurance exercise at improving 24-h glucose and blood lipid levels - Kim, Hyeon-Ki; Furuhashi, Shota; Takahashi, Masaki; Chijiki, Hanako; Nanba, Takuya; Inami, Takayuki; Radak, Zsolt; Sakamoto, Shizuo; Shibata, Shigenobu (Frontiers in Endocrinology, 2022)
Background: Glucose and lipid tolerance reportedly exhibit diurnal variations, being lower in the evening than in the morning. Therefore, the effects of exercise on glucose and blood lipid levels at different times of the day may differ. This study aimed to investigate the effects of short-term endurance exercise intervention in the morning versus late afternoon on 24-h blood glucose variability and blood lipid levels. Methods: Twelve healthy young men participated in a randomized crossover trial. The participants were assigned to morning (09:00–11:00) or late afternoon (16:00–18:00) endurance exercise for a week, consisting of supervised exercise sessions on Mondays, Wednesdays, and Fridays. In the morning and evening trials, the participants walked for 60 min on a treadmill at approximately 60% of maximal oxygen uptake (VO2max). Following a 2-week wash-out period, the participants performed the exercise training regimen at another time point. Continuous glucose monitoring was used to evaluate blood glucose fluctuations during each 24-h trial period. Blood samples were collected before and after each intervention to examine blood lipid and hormonal responses. Results: Examination of the area under the curve (AUC) of the glucose level changes for 24 h after the late afternoon versus morning exercise intervention revealed significantly lower values for the former versus the latter (P < 0.01). The AUC of glucose level changes after each meal was also lower after the late afternoon versus morning intervention, and significantly lower values were observed in the late afternoon versus morning trial for breakfast and dinner (P < 0.05, P < 0.01). In addition, a significant decrease in triglycerides (TG) and TG/high-density lipoprotein cholesterol (HDL-C) was noted after versus before the late afternoon intervention (P < 0.05). Conclusions: These results suggest that late afternoon endurance exercise is more effective than morning endurance exercise at improving 24-h glucose and triglyceride levels.